Discovery of novel and potent celastrol derivatives as PRDX1 inhibitors for cancer therapy through structure-based virtual screening - Guan, Lixia; Geng, Yifei; Wang, Yuting; Niu, Miao-Miao; Shi, Kun (Frontiers in Pharmacology, 2025)
BackgroundPeroxiredoxin 1 (PRDX1) is an antioxidant enzyme overexpressed in several cancers that protects tumor cells from oxidative damage by scavenging excess reactive oxygen species making it a potential strategy for cancer therapy.MethodsIn this study, a multi-step screening strategy combining molecular docking, enzyme inhibition assay, enzyme kinetic studies, molecular dynamics (MD) simulations, MST assays, MTT assays and in vivo toxicity assay was used to discover PRDX1 inhibitors.ResultsFive compounds (CPs 1–5) targeting PRDX1 were identified through molecular docking screening. CPs 1-5 showed significant PRDX1 inhibition at the nanomolar level. Among them, CP1 exhibited the most potent inhibitory activity (IC50 = 0.08 ± 0.01 nM) and high selectivity against PRDX1. The kinetic study showed that CP1 acted as noncompetitive PRDX1 inhibitor. MD simulations confirmed the stability of the CP1-PRDX1 complex. MST assays revealed that CP1 displayed a significant binding affinity for PRDX1 (Kd = 0.06 ± 0.001 nM). Importantly, CP1 exhibited significant antiproliferative effects on A549, HepG2 and MCF-7 tumor cells without toxicity to other normal cells. Meanwhile, CP1 did not exhibit significant hepatotoxicity or renal toxicity in mice.ConclusionThe results suggest that CP1 is a promising antitumor candidate for cancer therapy and merits further investigation.